Postmidnight bubbles and scintillations in the quiet‐time June solstice. Issue 21 (15th November 2013) - Yizengaw, E.; Retterer, J.; Pacheco, E. E.; Roddy, P.; Groves, K.; Caton, R.; Baki, P.
<x xml:space="preserve">Abstract</x> [1] While the mechanism for producing plasma irregularities in the dusk sector is believed to be fairly well understood, the cause of the formation of irregularities and bubbles during the postmidnight sector is still unknown, especially for magnetically quiet periods. This paper presents a case study of the strong postmidnight bubbles that often occur during magnetically quiet periods primarily in June solstice, along with a 4 year (2009–2012) statistical study that shows strong occurrence peak during June solstice predominantly in the African sector. We also confirm, for the first time, the presence of Rayleigh‐Taylor (RT) instability during postmidnight hours by using the physics‐based model for plasma densities and RT growth rates. Finally, we consider several possible sources of the eastward electric fields that permit the RT instability to develop and form bubbles in the postmidnight local time sector.